Sex-related differences in incidence, phenotype and risk of sudden cardiac death in inherited arrhythmia syndromes - Asatryan, Babken; Barth, Andreas S. (Frontiers in Cardiovascular Medicine, 2023)
Inherited Arrhythmia Syndromes (IAS) including long QT and Brugada Syndrome, are characterized by life-threatening arrhythmias in the absence of apparent structural heart disease and are caused by pathogenic variants in genes encoding cardiac ion channels or associated proteins. Studies of large pedigrees of families affected by IAS have demonstrated incomplete penetrance and variable expressivity. Biological sex is one of several factors that have been recognized to modulate disease severity in IAS. There is a growing body of evidence linking sex hormones to the susceptibility to arrhythmias, yet, many sex-specific disease aspects remain underrecognized as female sex and women with IAS are underinvestigated and findings from male-predominant cohorts are often generalized to both sexes with minimal to no consideration of relevant sex-associated differences in prevalence, disease manifestations and outcome. In this review, we highlight current knowledge of sex-related biological differences in normal cardiac electrophysiology and sex-associated factors that influence IAS phenotypes.